Analysis of prescription pattern of antihypertensives in various stages of chronic kidney disease - P., Prabitha; T., Reshmi; Jayakumar, K. P. (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Chronic kidney disease (CKD) is an emerging health problem and is one of the major causes of mortality. Hypertension is closely linked with CKD and both these conditions cause severe cardiovascular events. Hence blood pressure control is pertinent in all stages of CKD. This plays a major role in preventing its progression to end stage kidney disease and death. The objectives of the study were to analyse the class, dosing schedule of antihypertensive prescribed in Chronic Kidney Disease and the incidence of monotherapy and combination therapy. Methods: This study designed as a cross sectional study was conducted in Nephrology department of a tertiary care center and antihypertensive prescription pattern of 364 CKD patients was analyzed. Demographic details, the co-morbid factors and the details of drugs received by each patient were recorded from their outpatient/ inpatient charts. Data collected were entered in MS excel sheet and descriptive analysis done using SPSS software. Results: Calcium Channel Blocker (CCB) was the most commonly prescribed antihypertensive (70.6%) in all stages and the most common CCB was Cilnidipine (54%) with the dosing schedule of 20mg twice daily (56.4%). Incidence of combination therapy was 71.7% and CCB+AA (Alpha agonist) was the commonest combination prescribed in all stages except stage 1. Conclusions: CCBSs were widely prescribed as antihypertensive in CKD irrespective of the stages. Cilnidpine was the routinely prescribed CCB and seemed to be well tolerated by the patients. The protocol followed in this tertiary care center was in accordance with the standard guidelines by Kidney Disease Improving Global outcomes 2012.